Candida Antarctica As Catalyst For Polycaprolactone Synthesis: Effect Of Temperature And Solvents. - Arumugasamy, Senthil Kumar; Ahmad, Zainal (2010)

(untitled)
The Effects of temperature on ring-opening bulk polymerizations of ε-caprolactone was studied by using lipase Novozym 435 (immobilized form of lipase B from Candida antarctica), as biocatalyst.